The Use of Picture Series in Speaking Skill - Agustiawati, Hartini (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2020)
Teaching English is a challenging to teacher of English. They must work hard to teach, introduce and persuade students to learn. There are four skills in teaching English, such as listening, speaking, reading and writing. Among them, speaking will be challenging for students. They are afraid to talk and no self confidence to try speaking English. It is totally hard for students who learn English as a Foreign Language. They don’t have a place to practice their English. It makes students lazy to learn and speak English. In this case, teachers must be smart to find strategy or right technique. In order to improve students’ interest and ability a method can be used. Picture Series is one of the methods which is suitable to be applied in teaching students in the classroom. This method can motivate and inspire students to speak. Students will find ideas through the pictures. It is so helpful and useful in order to improve students’ speaking ability.